The Shapes of Sound. Organic Geometries, Harmonic Ratios and Ethnic Design (diségno, 2022)
The paper aims to highlight the connection between organic geometry, proportional ratios and the conformation of musical instru- ments: emblematic examples of a folk design that spontaneously combines art and technique, innovation and tradition, listening and vision. It is a process of analysis that, through direct survey, structure-from-motion techniques, three-dimensional modeling, and the study of geometries, aims to document ethnic shapes and traditions: traces that, over the centuries, have triggered processes of innovation based on experimentation ‘poor’ in material but rich in creativity.
Keywords: organic geometries; proportional ratios; polycentric curve; ethnic design; musical instruments